SEJARAH FILSAFAT ILMU PADA ABAD KONTEMPORER - Muhammad Qadafi; Ridha Ahida; Ali Akbar (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstract. Philosophy is not only seen as the parent and source of knowledge, but is also part of science itself, which also experiences specialization. In this transitional stage, philosophy does not cover the whole, but has become sectoral. For example, philosophy of religion, philosophy of law and philosophy of science are part of the development of philosophy which has become sectoral and focused in one particular field. In this context, science as a philosophical study is very relevant to study and deepen. Philosophy of Science is considered very necessary because this knowledge is closely related to scientific culture which is part of a person's life. The area of ​​study of philosophy does not only concern science and the various methods used to obtain knowledge. A framework of thinking that is only based on the paradigm of empiricist thinking with a number of induction logic and suggestions as well as tools for quantitative statistical thinking, or rationalism with a deductive-qualitative method with suggestions and tools for mathematical thinking, but also a metaphysical dimension which in certain contexts is broader than just demanding knowledge. This philosophy of science examines the development of science, the character of science from time to time, and how each character is influenced and influences the culture and civilization that surrounds it.